Anti-skid coating process for notebook computer shell surface

Through vacuum coating process and the use of modified mixed nanoparticles, Al-Ti, AlMnCe, cerium oxide and silica mixed coatings are formed, which solves the problem of weakening anti-slip performance and wear resistance of laptop shells, and achieves more lasting anti-slip and wear-resistant effect.

CN118639195BActive Publication Date: 2024-12-31DONGGUAN IRIDIUM TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410807082.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-21
Publication Date
2024-12-31
Estimated Expiration
2044-06-21

AI Technical Summary

Technical Problem

In the prior art, the anti-slip and wear resistance of the laptop case are easily weakened after long-term use, making it difficult to provide long-term effective protection, and the coating process is complicated, which adds additional operating steps.

Method used

The AlMnCe alloy target is used to deposit the Al-Ti transition layer, the AlMnCe layer, the cerium oxide and silica mixed coating layer through vacuum coating process, and the protective paint of modified mixed nanoparticles is applied to the coating layer to form an anti-slip coating layer. Improve the anti-slip and wear resistance of the shell.

Benefits of technology

Through Ce regulation and vacuum coating technology, a uniform and dense AlMnCe layer is formed, which enhances the binding force and anti-slip performance of the coating layer. Modified mixed nanoparticles improve the stability and surface roughness of the coating layer, and significantly improves the laptop shell. Anti-slip and wear resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present invention relates to the field of vacuum coating technology, and more specifically, it relates to an anti-skid coating process for the surface of a laptop computer shell. An anti-skid coating process for the surface of a laptop computer shell comprises the following steps: shell substrate pretreatment, AlMnCe alloy target material preparation, surface vacuum coating processing, coating layer protective paint preparation and coating layer protective treatment. The present invention forms an Al-Ti transition layer, an AlMnCe layer, a cerium oxide and silicon dioxide mixed coating layer by sequentially depositing on the surface of the shell substrate. The Al-Ti transition layer, the AlMnCe layer, the cerium oxide and silicon dioxide mixed coating layer together constitute the coating layer, which helps to increase the hand resistance of the shell substrate surface, improve the wear resistance and anti-skid performance of the shell substrate surface, and the coating layer is coated with protective paint on the surface of the coating layer, which can further increase the surface roughness of the coating layer and further improve the anti-skid performance of the laptop computer shell.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of vacuum coating, and more particularly to an anti-skid coating process for the surface of a notebook computer shell. Background Art

[0002] The laptop shell is mainly used to protect the body of the laptop computer. It can provide physical protection for sensitive components inside the laptop computer, such as the display screen, processor, hard disk, memory stick, etc., to resist external impact, pressure, dust and moisture, prevent damage to the body, and extend the life of the device. Compared with desktop computers, laptop computers are lighter and easier to carry, which makes it easy for the laptop computer to inevitably rub or collide with other objects during use. If the laptop shell is not hard enough, it will not only cause friction damage to the laptop shell, but also cause the screen to be compressed and deformed or the body to be damaged, thus shortening the life of the laptop computer.

[0003] In order to reduce the friction or impact between the laptop computer shell and other objects, in the prior art, in addition to selecting a high-hardness material with good wear resistance as the shell substrate, the wear resistance and anti-slip performance of the laptop computer shell are improved by designing printed textures, laser engraving concave-convex patterns or attaching anti-slip rubber gaskets, etc., to increase the friction between the laptop computer shell and other objects or hand-held, so as to improve the stability of the laptop computer when placed or held, and reduce the friction or impact between the laptop computer shell and other objects. However, the above method requires that the laptop computer shell be processed after the coating treatment is completed, which increases the surface treatment operation steps of the laptop computer shell. In addition, there are still problems such as poor adhesion and the wear resistance and anti-slip performance will gradually weaken after long-term touch or scratching, making it difficult to provide long-term and effective protection for the laptop computer shell.

[0004] Therefore, it is of great significance to develop an anti-skid coating process that can effectively improve the wear resistance and anti-skid performance of the notebook computer shell during the coating process of the notebook computer shell. Summary of the invention

[0005] In view of the deficiencies of the prior art, the present invention provides a non-slip coating process for the surface of a notebook computer shell.

[0006] A non-slip coating process for the surface of a notebook computer shell comprises the following steps:

[0007] S1: pretreatment of the shell substrate, ultrasonic cleaning and surface treatment of the shell substrate, so that the surface of the shell substrate is kept clean, and the roughness of the surface of the shell substrate Ra ≤ 0.5 μm;

[0008] S2: Preparation of AlMnCe alloy target, using high-purity metal Al, Mn, Ce as initial raw materials, after smelting, casting, vacuum degassing, cutting and surface grinding and polishing, AlMnCe alloy target is obtained, wherein the Ce addition amount is 8-12% of the total mass of Al and Mn;

[0009] S3: Surface vacuum coating processing, after completing the pretreatment of the shell substrate, the shell substrate is placed under vacuum conditions, an inert gas is introduced, and an aluminum target and a titanium target are sputtered onto the surface of the shell substrate to deposit an Al-Ti transition layer. The inert gas is continuously introduced, and an AlMnCe alloy target is sputtered onto the surface of the shell substrate, and an AlMnCe layer is deposited on the Al-Ti transition layer. An inert gas and oxygen are introduced, and a silicon target and a cerium target are sputtered onto the surface of the shell substrate, and a cerium oxide and silicon dioxide mixed coating layer is deposited on the AlMnCe layer. After the coating is completed, only oxygen is introduced, and the shell substrate is heated and heat-insulated to complete the surface vacuum coating processing of the shell substrate, and obtain the shell substrate after the coating processing;

[0010] S4: preparing a coating layer protective paint and performing a coating layer protective treatment, preparing a coating layer protective paint, and spraying the coating layer protective paint on the surface of the shell substrate after the coating process by electrostatic spraying to form a coating protective layer, thereby obtaining a laptop shell after coating protection;

[0011] The coating layer is coated with a protective paint prepared by mixing 50 to 70 parts by weight of an organic silicon acrylic resin, 0.5 to 3 parts by weight of an organic silicon defoamer, 0.3 to 2 parts by weight of dimethylsiloxane, 4 to 10 parts by weight of a curing agent, and 2 to 8 parts by weight of modified mixed nanoparticles;

[0012] The silicone acrylic resin is prepared by stirring and mixing 20 to 30 parts by weight of methyl acrylate, 25 to 40 parts by weight of methyl methacrylate, 20 to 35 parts by weight of styrene, 5 to 12 parts by weight of hydroxyethyl acrylate, 2 to 7 parts by weight of acrylic acid and 0.6 to 3 parts by weight of dibenzoyl peroxide, and then slowly dripping into a mixed solution of ethyl acetate, butyl acetate and polydimethylsiloxane to obtain the organic silicone acrylic resin through a polymerization reaction. The mixed solution of ethyl acetate, butyl acetate and polydimethylsiloxane is prepared by mixing 25 to 35 parts by weight of ethyl acetate, 16 to 40 parts by weight of butyl acetate and 7 to 18 parts by weight of polydimethylsiloxane.

[0013] The modified hybrid nanoparticles are obtained by mixing nano-silicon dioxide and nano-titanium dioxide and then modifying them with a coupling agent KH-570.

[0014] Furthermore, the shell substrate is titanium alloy, aluminum-magnesium alloy or magnesium-aluminum alloy.

[0015] Furthermore, the surface treatment is at least one of a grinding operation, a sandblasting operation or a shot peening operation.

[0016] Furthermore, step S2 AlMnCe alloy target material preparation specifically includes the following steps:

[0017] S2.1: Using high-purity metals Al, Mn, and Ce as initial raw materials, the mass ratio of Al to Mn is (10-20):(1-5), and the amount of Ce added is 8-12% of the total mass of Al and Mn. In an inert gas atmosphere, Al, Mn, and Ce are melted and mixed into an alloy liquid, and the alloy liquid is poured into a mold for casting to obtain an AlMnCe alloy ingot;

[0018] S2.2: After vacuum degassing of the AlMnCe alloy ingot, cutting and surface grinding and polishing are performed to obtain the AlMnCe alloy target.

[0019] Furthermore, step S3 of surface vacuum coating processing specifically includes the following steps:

[0020] S3.1: After the shell substrate is pretreated, the shell substrate is placed in a vacuum furnace and the vacuum furnace is evacuated to a background vacuum with a vacuum degree of 3 to 6×10 -3 Pa, heat the shell substrate in the vacuum furnace to 70-90°C;

[0021] S3.2: Load the aluminum target into the sputtering target A, load the titanium target into the sputtering target B, introduce an inert gas into the vacuum furnace, the inert gas flow rate is 200-400 sccm, the gas pressure is controlled at 0.1-1 Pa, and the sputtering power supplies of the sputtering targets A and B are turned on at the same time, the current of the sputtering target A is 25-30A, and the current of the sputtering target B is 20-25A, and the aluminum target and the titanium target are sputtered onto the surface of the shell substrate, so that a layer of Al-Ti transition layer with a thickness of 100-150nm is deposited on the surface of the shell substrate;

[0022] S3.3: Replace the aluminum target material in the sputtering target A with an AlMnCe alloy target material, continue to introduce an inert gas into the vacuum furnace, the inert gas flow rate is 200-400 sccm, the gas pressure is controlled at 0.1-1 Pa, turn on the sputtering power supply of the sputtering target A, the current of the sputtering target A is 20-30 A, and sputter the AlMnCe alloy target material onto the surface of the shell substrate, and deposit a layer of AlMnCe with a thickness of 150-200 nm on the Al-Ti transition layer;

[0023] S3.4: Replace the AlMnCe alloy target in sputtering target A with a silicon target, replace the titanium target in sputtering target B with a cerium target, introduce inert gas and oxygen into the vacuum furnace, the inert gas flow rate is 200-400sccm, the oxygen flow rate is 150-300sccm, and the gas pressure is controlled at 0.5-1.5Pa. At the same time, turn on the sputtering power supplies of sputtering target A and sputtering target B, the current of sputtering target A is 25-30A, and the current of sputtering target B is 25-30A. Sputter the silicon target and the cerium target onto the surface of the shell substrate, and deposit a cerium oxide and silicon dioxide mixed coating layer with a thickness of 100-200nm on the AlMnCe layer. The Al-Ti transition layer, the AlMnCe layer, and the cerium oxide and silicon dioxide mixed coating layer together constitute a coating layer from bottom to top;

[0024] S3.5: After the coating is completed, stop the introduction of inert gas, and only introduce oxygen into the vacuum furnace. The oxygen flow rate is 150-300sccm. The shell substrate is heated at a temperature of 400-600°C and kept warm for 20-30 minutes to complete the surface vacuum coating of the shell substrate and obtain the shell substrate after coating.

[0025] Furthermore, the inert gas is any one of helium, neon, argon, krypton or xenon.

[0026] Furthermore, step S4 of coating the coating layer with protective paint preparation and coating the coating layer with protective treatment specifically includes the following steps:

[0027] S4.1: 20 to 30 parts by weight of methyl acrylate, 25 to 40 parts by weight of methyl methacrylate, 20 to 35 parts by weight of styrene, 5 to 12 parts by weight of hydroxyethyl acrylate and 2 to 7 parts by weight of acrylic acid are mixed and stirred, and then 0.6 to 3 parts by weight of dibenzoyl peroxide are added, and the mixture is stirred evenly to obtain an acrylic monomer mixture;

[0028] S4.2: 25-35 parts by weight of ethyl acetate, 16-40 parts by weight of butyl acetate and 7-18 parts by weight of polydimethylsiloxane are sequentially added into a reaction kettle, heated to 72-80° C. under a nitrogen atmosphere, stirred continuously for 20-30 minutes, and then heated to 100-110° C. The acrylic acid monomer mixture obtained in step S4.1 is slowly dripped into the reaction kettle, and polymerized under azeotropic distillation conditions at 100-110° C. for 1-2 hours to obtain a silicone acrylic resin;

[0029] S4.3: 1 to 5 parts by weight of nano-silicon dioxide and 1 to 5 parts by weight of nano-titanium dioxide are mixed to obtain mixed nano-particles, the mixed nano-particles are dissolved in 20 to 40 parts by weight of N-methylpyrrolidone, and ultrasonically dispersed for 20 to 30 minutes, and then 6 to 30 parts by weight of coupling agent KH-570 are slowly added dropwise under the condition of ultrasonic dispersion, and reacted for 1 to 2 hours under a nitrogen atmosphere. After the reaction is completed, the modified mixed nano-particles are obtained by centrifugal separation, filtration, and washing;

[0030] S4.4: 50 to 70 parts by weight of silicone acrylic resin, 0.5 to 3 parts by weight of silicone defoamer, and 0.3 to 2 parts by weight of dimethylsiloxane are added to a reactor, and after uniform mixing, 4 to 10 parts by weight of curing agent and 2 to 8 parts by weight of modified mixed nanoparticles are added, and ultrasonic dispersion is performed for 20 to 40 minutes to obtain a coating layer coated with protective paint;

[0031] S4.5: The coating layer is coated with protective paint by electrostatic spraying on the surface of the shell substrate after coating. Subsequently, the shell substrate after spraying is placed in a drying oven and dried and cured at 50-60°C for 2-5 hours to form a coating protective layer. The coating layer protection treatment is completed to obtain a laptop shell after coating protection.

[0032] Furthermore, the diameter of the nano-silicon dioxide is 10 to 80 nm.

[0033] Furthermore, the diameter of nano-titanium dioxide is 10 to 50 nm.

[0034] Furthermore, the curing agent is hexamethylene diisocyanate.

[0035] The present invention has the following advantages:

[0036] 1. In the present invention, the Ce content in the AlMnCe alloy target is adjusted to 8-12% of the total mass of Al and Mn, which is helpful to form Al 10 The CeMn2 primary phase prevents the Al-Mn precipitate phase from overgrowing to form a coarse columnar dendrite structure, avoids brittle cracking of the alloy target during use, and ensures that the coating operation is normal and effective. Moreover, after the vacuum coating process, the addition of Ce helps to promote the Al-Mn-based coating to form an amorphous structure. The formed AlMnCe layer has a uniform and dense structure, which helps to improve the wear resistance of the shell substrate surface and the bonding strength between the AlMnCe layer and the Al-Ti transition layer.

[0037] 2. In the present invention, inert gas and oxygen are introduced under vacuum conditions, and silicon target materials and cerium target materials are sputtered onto the surface of the shell substrate. The cerium oxide and silicon dioxide mixed coating formed by sputtering has a matte frosted texture, which is beneficial to increase the hand resistance of the shell substrate surface and improve the anti-slip performance of the shell substrate surface.

[0038] 3. In the present invention, after the coating protective paint obtained by dispersing and mixing the modified mixed nanoparticles in the silicone acrylic resin is applied to the surface of the coating layer, the formed coating protective layer can not only effectively adhere to the surface of the coating layer to enhance the stability and stain resistance of the coating layer, but also the modified mixed nanoparticles in the coating protective layer can be well dispersed on the surface of the coating layer, increase the surface roughness of the coating layer surface, and further improve the anti-slip performance of the laptop computer casing. DETAILED DESCRIPTION

[0039] In order to enable persons skilled in the art to better understand the technical solutions in the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Example

[0040] A non-slip coating process for the surface of a notebook computer shell comprises the following steps:

[0041] S1: Shell substrate pretreatment,

[0042] S1.1: Place the shell substrate in an ultrasonic cleaning machine and perform ultrasonic cleaning in petroleum ether and anhydrous ethanol for 20 minutes in sequence. The ultrasonic cleaning power is 500W to remove impurities such as grease, dust, oxide layer, etc. on the surface of the shell substrate;

[0043] S1.2: Put the cleaned shell substrate into a sandblasting machine, and perform sandblasting on the surface of the cleaned shell substrate so that the roughness Ra of the shell substrate surface is ≤ 0.5 μm, thereby enhancing the adhesion of the coating;

[0044] S2: AlMnCe alloy target preparation,

[0045] S2.1: Using high-purity metals Al, Mn, and Ce as initial raw materials, the mass ratio of Al to Mn is 4:1, and the Ce addition amount is 12% of the total mass of Al and Mn. Using a vacuum induction melting furnace under the protection of argon, Al, Mn, and Ce are melted and mixed into an alloy liquid, and the alloy liquid is poured into a pre-prepared mold for casting to obtain an AlMnCe alloy ingot;

[0046] S2.2: After vacuum degassing the AlMnCe alloy ingot, cutting and surface grinding and polishing are performed to obtain the AlMnCe alloy target;

[0047] S3: Surface vacuum coating processing,

[0048] S3.1: After the shell substrate pretreatment is completed, the shell substrate is placed in a vacuum furnace and the vacuum furnace is evacuated to a background vacuum with a vacuum degree of 6×10 -3 Pa, the shell substrate in the vacuum furnace is heated to 90°C by a heater, so that the metal atomic structure on the surface of the shell substrate changes, making the metal atoms in an active state;

[0049] S3.2: Load the aluminum target into the sputtering target A, load the titanium target into the sputtering target B, introduce argon gas into the vacuum furnace, the argon gas flow rate is 400 sccm, and the gas pressure is controlled at 0.8 Pa. At the same time, turn on the sputtering power of the sputtering target A and the sputtering target B, the current of the sputtering target A is 30A, and the current of the sputtering target B is 25A. Sputter the aluminum target and the titanium target onto the surface of the shell substrate to deposit an Al-Ti transition layer with a thickness of 150nm;

[0050] S3.3: Replace the aluminum target material in the sputtering target A with an AlMnCe alloy target material, continue to introduce argon gas into the vacuum furnace, the argon gas flow rate is 400 sccm, the gas pressure is controlled at 0.8 Pa, turn on the sputtering power supply of the sputtering target A, the current of the sputtering target A is 30 A, and sputter the AlMnCe alloy target material onto the surface of the shell substrate, and deposit a 200 nm thick AlMnCe layer on the Al-Ti transition layer;

[0051] S3.4: Replace the AlMnCe alloy target in sputtering target A with a silicon target, and replace the titanium target in sputtering target B with a cerium target. Introduce argon and oxygen into the vacuum furnace. The argon flow rate is 400 sccm, the oxygen flow rate is 300 sccm, and the gas pressure is controlled at 1.5 Pa. At the same time, turn on the sputtering power supplies of sputtering target A and sputtering target B. The current of sputtering target A is 30 A, and the current of sputtering target B is 30 A. Sputter the silicon target and the cerium target onto the surface of the shell substrate, and deposit a cerium oxide and silicon dioxide mixed coating layer with a thickness of 200 nm on the AlMnCe layer. The Al-Ti transition layer, the AlMnCe layer, and the cerium oxide and silicon dioxide mixed coating layer together constitute a coating layer from bottom to top;

[0052] S3.5: After the coating is completed, the introduction of argon gas is stopped, and only oxygen is introduced into the vacuum furnace, and the oxygen flow rate is 300 sccm. The shell substrate is heated to 600°C and kept warm for 30 minutes to complete the surface vacuum coating of the shell substrate, and obtain the shell substrate after coating;

[0053] S4: Preparation of coating protective paint for coating layer and coating protective treatment for coating layer,

[0054] S4.1: 30 parts by weight of methyl acrylate, 40 parts by weight of methyl methacrylate, 35 parts by weight of styrene, 12 parts by weight of hydroxyethyl acrylate and 7 parts by weight of acrylic acid are mixed, and then 2 parts by weight of dibenzoyl peroxide are added and stirred to obtain an acrylic monomer mixture;

[0055] S4.2: 35 parts by weight of ethyl acetate, 40 parts by weight of butyl acetate and 18 parts by weight of polydimethylsiloxane are added to a reaction kettle in sequence, heated to 80°C under a nitrogen atmosphere, stirred continuously for 30 minutes, and then heated to 110°C. The acrylic acid monomer mixture obtained in step S4.1 is slowly dripped into the reaction kettle, and polymerized under azeotropic distillation conditions at 110°C for 2 hours to obtain a silicone acrylic resin;

[0056] S4.3: 5 parts by weight of nano-silicon dioxide and 5 parts by weight of nano-titanium dioxide are mixed to obtain mixed nano-particles, wherein the diameter of the nano-silicon dioxide is 50 nm, and the diameter of the nano-titanium dioxide is 50 nm. The mixed nano-particles are dissolved in 40 parts by weight of N-methylpyrrolidone, and ultrasonically dispersed for 30 minutes. Then, 30 parts by weight of coupling agent KH-570 are slowly added dropwise under the condition of ultrasonic dispersion, and reacted for 2 hours under a nitrogen atmosphere. After the reaction is completed, the modified mixed nano-particles are obtained by centrifugation, filtration, and washing.

[0057] S4.4: 70 parts by weight of silicone acrylic resin, 3 parts by weight of silicone defoamer, and 2 parts by weight of dimethylsiloxane are added to a reactor, and after being evenly mixed, 10 parts by weight of hexamethylene diisocyanate and 8 parts by weight of modified mixed nanoparticles are added, and ultrasonic dispersion is performed for 40 minutes to obtain a coating layer coated with protective paint;

[0058] S4.5: The coating layer is coated with protective paint by electrostatic spraying on the surface of the shell substrate after coating. Subsequently, the shell substrate after spraying is placed in a drying oven and dried and cured at 60°C for 3 hours to form a coating protective layer. The coating layer coating protection treatment is completed to obtain a laptop shell after coating protection. Example

[0059] A non-slip coating process for the surface of a notebook computer shell comprises the following steps:

[0060] S1: Shell substrate pretreatment,

[0061] S1.1: Place the shell substrate in an ultrasonic cleaning machine and perform ultrasonic cleaning in petroleum ether and anhydrous ethanol for 20 minutes in sequence. The ultrasonic cleaning power is 500W to remove impurities such as grease, dust, oxide layer, etc. on the surface of the shell substrate;

[0062] S1.2: Put the cleaned shell substrate into a sandblasting machine, and perform sandblasting on the surface of the cleaned shell substrate so that the roughness Ra of the shell substrate surface is ≤ 0.5 μm, thereby enhancing the adhesion of the coating;

[0063] S2: AlMnCe alloy target preparation,

[0064] S2.1: Using high-purity metals Al, Mn, and Ce as initial raw materials, the mass ratio of Al to Mn is 4:1, and the Ce addition amount is 12% of the total mass of Al and Mn. Using a vacuum induction melting furnace under the protection of argon, Al, Mn, and Ce are melted and mixed into an alloy liquid, and the alloy liquid is poured into a pre-prepared mold for casting to obtain an AlMnCe alloy ingot;

[0065] S2.2: After vacuum degassing the AlMnCe alloy ingot, cutting and surface grinding and polishing are performed to obtain the AlMnCe alloy target;

[0066] S3: Surface vacuum coating processing,

[0067] S3.1: After the shell substrate pretreatment is completed, the shell substrate is placed in a vacuum furnace and the vacuum furnace is evacuated to a background vacuum with a vacuum degree of 3×10 -3 Pa, the shell substrate in the vacuum furnace is heated to 70°C by a heater, so that the metal atomic structure on the surface of the shell substrate changes, making the metal atoms in an active state;

[0068] S3.2: Load the aluminum target into the sputtering target A, load the titanium target into the sputtering target B, introduce argon gas into the vacuum furnace, the argon gas flow rate is 200 sccm, and the gas pressure is controlled at 0.5 Pa. At the same time, turn on the sputtering power of the sputtering target A and the sputtering target B, the current of the sputtering target A is 25A, and the current of the sputtering target B is 20A. Sputter the aluminum target and the titanium target onto the surface of the shell substrate to deposit an Al-Ti transition layer with a thickness of 100 nm;

[0069] S3.3: Replace the aluminum target material in the sputtering target A with an AlMnCe alloy target material, continue to introduce argon gas into the vacuum furnace, the argon gas flow rate is 200 sccm, the gas pressure is controlled at 0.5 Pa, turn on the sputtering power supply of the sputtering target A, the current of the sputtering target A is 20 A, and sputter the AlMnCe alloy target material onto the surface of the shell substrate, and deposit a 150 nm thick AlMnCe layer on the Al-Ti transition layer;

[0070] S3.4: Replace the AlMnCe alloy target in sputtering target A with a silicon target, and replace the titanium target in sputtering target B with a cerium target. Introduce argon and oxygen into the vacuum furnace. The argon flow rate is 200 sccm, the oxygen flow rate is 150 sccm, and the gas pressure is controlled at 1 Pa. At the same time, turn on the sputtering power supplies of sputtering target A and sputtering target B. The current of sputtering target A is 25 A, and the current of sputtering target B is 25 A. Sputter the silicon target and the cerium target onto the surface of the shell substrate, and deposit a 100 nm thick cerium oxide and silicon dioxide mixed coating layer on the AlMnCe layer. The Al-Ti transition layer, the AlMnCe layer, and the cerium oxide and silicon dioxide mixed coating layer together constitute a coating layer from bottom to top;

[0071] S3.5: After the coating is completed, the introduction of argon gas is stopped, and only oxygen is introduced into the vacuum furnace, and the oxygen flow rate is 150 sccm. The shell substrate is heated to a temperature of 500° C. and kept warm for 20 minutes to complete the surface vacuum coating of the shell substrate, and obtain the shell substrate after coating;

[0072] S4: Preparation of coating protective paint for coating layer and coating protective treatment for coating layer,

[0073] S4.1: 30 parts by weight of methyl acrylate, 40 parts by weight of methyl methacrylate, 35 parts by weight of styrene, 12 parts by weight of hydroxyethyl acrylate and 7 parts by weight of acrylic acid are mixed, and then 2 parts by weight of dibenzoyl peroxide are added and stirred to obtain an acrylic monomer mixture;

[0074] S4.2: 35 parts by weight of ethyl acetate, 40 parts by weight of butyl acetate and 18 parts by weight of polydimethylsiloxane are added to a reaction kettle in sequence, heated to 72° C. under a nitrogen atmosphere, stirred continuously for 20 min, and then heated to 100° C. The acrylic acid monomer mixture obtained in step S4.1 is slowly dripped into the reaction kettle, and polymerized under azeotropic distillation conditions at 100° C. for 1 h to obtain an organosilicon acrylic resin;

[0075] S4.3: 5 parts by weight of nano-silicon dioxide and 5 parts by weight of nano-titanium dioxide are mixed to obtain mixed nano-particles, wherein the diameter of the nano-silicon dioxide is 50 nm, and the diameter of the nano-titanium dioxide is 50 nm. The mixed nano-particles are dissolved in 40 parts by weight of N-methylpyrrolidone, and ultrasonically dispersed for 20 minutes. Then, 30 parts by weight of coupling agent KH-570 are slowly added dropwise under the condition of ultrasonic dispersion, and reacted for 1 hour under a nitrogen atmosphere. After the reaction is completed, the modified mixed nano-particles are obtained by centrifugation, filtration, and washing.

[0076] S4.4: 70 parts by weight of silicone acrylic resin, 3 parts by weight of silicone defoamer, and 2 parts by weight of dimethylsiloxane are added to a reactor, and after being evenly mixed, 10 parts by weight of hexamethylene diisocyanate and 8 parts by weight of modified mixed nanoparticles are added, and ultrasonic dispersion is performed for 20 minutes to obtain a coating layer coated with protective paint;

[0077] S4.5: The coating layer is coated with protective paint by electrostatic spraying on the surface of the shell substrate after coating. Subsequently, the shell substrate after spraying is placed in a drying oven and dried and cured at 50°C for 3 hours to form a coating protective layer. The coating layer protection treatment is completed to obtain a laptop shell after coating protection. Example

[0078] A non-slip coating process for the surface of a notebook computer shell comprises the following steps:

[0079] S1: Shell substrate pretreatment,

[0080] S1.1: Place the shell substrate in an ultrasonic cleaning machine and perform ultrasonic cleaning in petroleum ether and anhydrous ethanol for 20 minutes in sequence. The ultrasonic cleaning power is 500W to remove impurities such as grease, dust, oxide layer, etc. on the surface of the shell substrate;

[0081] S1.2: Put the cleaned shell substrate into a sandblasting machine, and perform sandblasting on the surface of the cleaned shell substrate so that the roughness Ra of the shell substrate surface is ≤ 0.5 μm, thereby enhancing the adhesion of the coating;

[0082] S2: AlMnCe alloy target preparation,

[0083] S2.1: Using high-purity metals Al, Mn, and Ce as initial raw materials, the mass ratio of Al to Mn is 10:1, and the amount of Ce added is 8% of the total mass of Al and Mn. Using a vacuum induction melting furnace under the protection of argon, Al, Mn, and Ce are melted and mixed into an alloy liquid, and the alloy liquid is poured into a pre-prepared mold for casting to obtain an AlMnCe alloy ingot;

[0084] S2.2: After vacuum degassing the AlMnCe alloy ingot, cutting and surface grinding and polishing are performed to obtain the AlMnCe alloy target;

[0085] S3: Surface vacuum coating processing,

[0086] S3.1: After the shell substrate pretreatment is completed, the shell substrate is placed in a vacuum furnace and the vacuum furnace is evacuated to a background vacuum with a vacuum degree of 6×10 -3 Pa, the shell substrate in the vacuum furnace is heated to 90°C by a heater, so that the metal atomic structure on the surface of the shell substrate changes, making the metal atoms in an active state;

[0087] S3.2: Load the aluminum target into the sputtering target A, load the titanium target into the sputtering target B, introduce argon gas into the vacuum furnace, the argon gas flow rate is 400 sccm, and the gas pressure is controlled at 0.8 Pa. At the same time, turn on the sputtering power of the sputtering target A and the sputtering target B, the current of the sputtering target A is 30A, and the current of the sputtering target B is 25A. Sputter the aluminum target and the titanium target onto the surface of the shell substrate to deposit an Al-Ti transition layer with a thickness of 150nm;

[0088] S3.3: Replace the aluminum target material in the sputtering target A with an AlMnCe alloy target material, continue to introduce argon gas into the vacuum furnace, the argon gas flow rate is 400 sccm, the gas pressure is controlled at 0.8 Pa, turn on the sputtering power supply of the sputtering target A, the current of the sputtering target A is 30 A, and sputter the AlMnCe alloy target material onto the surface of the shell substrate, and deposit a 200 nm thick AlMnCe layer on the Al-Ti transition layer;

[0089] S3.4: Replace the AlMnCe alloy target in sputtering target A with a silicon target, and replace the titanium target in sputtering target B with a cerium target. Introduce argon and oxygen into the vacuum furnace. The argon flow rate is 400 sccm, the oxygen flow rate is 300 sccm, and the gas pressure is controlled at 1.5 Pa. At the same time, turn on the sputtering power supplies of sputtering target A and sputtering target B. The current of sputtering target A is 30 A, and the current of sputtering target B is 30 A. Sputter the silicon target and the cerium target onto the surface of the shell substrate, and deposit a cerium oxide and silicon dioxide mixed coating layer with a thickness of 200 nm on the AlMnCe layer. The Al-Ti transition layer, the AlMnCe layer, and the cerium oxide and silicon dioxide mixed coating layer together constitute a coating layer from bottom to top;

[0090] S3.5: After the coating is completed, the introduction of argon gas is stopped, and only oxygen is introduced into the vacuum furnace, and the oxygen flow rate is 300 sccm. The shell substrate is heated to 600°C and kept warm for 30 minutes to complete the surface vacuum coating of the shell substrate, and obtain the shell substrate after coating;

[0091] S4: Preparation of coating protective paint for coating layer and coating protective treatment for coating layer,

[0092] S4.1: 20 parts by weight of methyl acrylate, 25 parts by weight of methyl methacrylate, 20 parts by weight of styrene, 5 parts by weight of hydroxyethyl acrylate and 2 parts by weight of acrylic acid are mixed, and then 0.6 parts by weight of dibenzoyl peroxide are added and stirred to obtain an acrylic monomer mixture;

[0093] S4.2: 25 parts by weight of ethyl acetate, 16 parts by weight of butyl acetate and 7 parts by weight of polydimethylsiloxane are added to a reaction kettle in sequence, heated to 80°C under a nitrogen atmosphere, stirred continuously for 30 minutes, and then heated to 110°C. The acrylic acid monomer mixture obtained in step S4.1 is slowly dripped into the reaction kettle, and polymerized under azeotropic distillation conditions at 110°C for 2 hours to obtain a silicone acrylic resin;

[0094] S4.3: 1 part by weight of nano-silicon dioxide and 1 part by weight of nano-titanium dioxide are mixed to obtain mixed nanoparticles, wherein the diameter of the nano-silicon dioxide is 50 nm, and the diameter of the nano-titanium dioxide is 50 nm. The mixed nanoparticles are dissolved in 20 parts by weight of N-methylpyrrolidone, and ultrasonically dispersed for 30 minutes. Then, 6 parts by weight of coupling agent KH-570 are slowly added dropwise under the condition of ultrasonic dispersion, and reacted for 2 hours under a nitrogen atmosphere. After the reaction is completed, the modified mixed nanoparticles are obtained by centrifugation, filtration, and washing.

[0095] S4.4: 50 parts by weight of silicone acrylic resin, 0.5 parts by weight of silicone defoamer, and 0.3 parts by weight of dimethylsiloxane are added to a reactor, and after being uniformly mixed, 4 parts by weight of hexamethylene diisocyanate and 2 parts by weight of modified mixed nanoparticles are added, and ultrasonic dispersion is performed for 40 minutes to obtain a coating layer coated with protective paint;

[0096] S4.5: The coating layer is coated with protective paint by electrostatic spraying on the surface of the shell substrate after coating. Subsequently, the shell substrate after spraying is placed in a drying oven and dried and cured at 60°C for 3 hours to form a coating protective layer. The coating layer coating protection treatment is completed to obtain a laptop shell after coating protection.

[0097] Comparative Example 1

[0098] The difference between this comparative example and Example 1 is that the addition amount of Ce in the AlMnCe alloy target is adjusted to 6% of the total mass of Al and Mn, and the other steps remain unchanged to prepare the AlMnCe alloy target, and deposit an Al-Ti transition layer and an AlMnCe layer on the surface of the shell substrate in sequence, which is recorded as Comparative Example 1.

[0099] Comparative Example 2

[0100] The difference between this comparative example and Example 1 is that the addition amount of Ce in the AlMnCe alloy target is adjusted to 15% of the total mass of Al and Mn, and the other steps remain unchanged to prepare the AlMnCe alloy target, and deposit an Al-Ti transition layer and an AlMnCe layer on the surface of the shell substrate in sequence, which is recorded as Comparative Example 2.

[0101] Comparative Example 3

[0102] The difference between this comparative example and Example 1 is that the Ce component in the AlMnCe alloy target is removed, and the other steps remain unchanged to prepare the AlMn alloy target, and the AlMnCe alloy target in step S3.3 is replaced by an AlMn alloy target, and an Al-Ti transition layer and an AlMn layer are sequentially deposited on the surface of the shell substrate, which is recorded as Comparative Example 3.

[0103] In Examples 1-3, after the Al-Ti transition layer and the AlMnCe layer were deposited on the surface of the shell substrate in sequence, the shell substrates were grouped according to Examples 1-3 and Comparative Examples 1-3, and 4 shell substrates each were selected as test samples from the shell substrates with Al-Ti transition layers and AlMnCe layers attached in Examples 1-3, the shell substrates with Al-Ti transition layers and AlMnCe layers attached in Comparative Examples 1-3, and the shell substrates with Al-Ti transition layers and AlMn layers attached in Comparative Example 3.

[0104] According to GB / T9286-2021 standard, the adhesion of 2 test samples in each group was tested; the wear resistance of the remaining 2 test samples in each group was tested: first, a contact angle meter was used to test the contact angle of water on each group of test samples, and the average contact angle of each group of test samples before friction was recorded. Then, each group of test samples was taken out from the contact angle meter, and steel wool was used to fit the surface of each group of test samples, and the steel wool was pushed back and forth to rub the surface of each group of test samples. The friction force applied was the same. After 500 back and forth frictions, the contact angle meter was used again to test the contact angle of water on each test sample, and the average contact angle of each group of test samples after friction was recorded. (The wear resistance was judged by the change in the contact angle before and after friction) The results are shown in Table 1 below.

[0105]

[0106] As shown in Table 1, after the addition amount of Ce in Comparative Examples 1 and 3 was adjusted to 6% and 0% of the total mass of Al and Mn, respectively, on the basis of Example 1, the coating adhesion was significantly reduced, while the coating adhesion of the AlMnCe layer of Examples 1-3 was good, indicating that the addition of Ce in the alloy target and the addition amount of Ce in the AlMnCe alloy target set to 8-12% of the total mass of Al and Mn can effectively improve the bonding force between the Al-Ti transition layer and the AlMnCe layer. Furthermore, after the wear resistance test of each group of test samples, the contact angle test results of the AlMnCe layer of Examples 1-3 before and after friction changed little, and only slight wear existed, indicating excellent wear resistance, while the contact angle test results of Comparative Examples 1-3 before and after friction changed relatively significantly, that is, a large degree of wear occurred, so it can be seen that the addition amount of Ce in the AlMnCe alloy target is controlled to 8-12% of the total mass of Al and Mn, which can effectively ensure the wear resistance of the AlMnCe layer to the surface of the shell substrate.

[0107] Comparative Example 4

[0108] The difference between this comparative example and Example 1 is that in step S3.4, only the sputtering power of sputtering target A is turned on, the silicon target material is sputtered onto the surface of the shell substrate, and a layer of silicon dioxide coating is deposited on the AlMnCe layer. The coating layer is composed of an Al-Ti transition layer, an AlMnCe layer, and a silicon dioxide coating from bottom to top. The other steps remain unchanged, and the shell substrate after coating is prepared, which is recorded as Comparative Example 4.

[0109] Comparative Example 5

[0110] The difference between this comparative example and Example 1 is that, in step S3.4, only the sputtering power of sputtering target B is turned on, the cerium target material is sputtered onto the surface of the shell substrate, and a layer of cerium oxide coating is deposited on the AlMnCe layer. The coating layer is composed of an Al-Ti transition layer, an AlMnCe layer, and a cerium oxide coating from bottom to top. The other steps remain unchanged, and the shell substrate after coating is prepared, which is recorded as Comparative Example 5.

[0111] In Examples 1-3, an Al-Ti transition layer, an AlMnCe layer, and a cerium oxide and silicon dioxide mixed coating layer are sequentially deposited on the surface of the shell substrate to obtain a coated shell substrate. The shell substrates are grouped according to Examples 1-3 and Comparative Examples 4-5. From the coated shell substrates of each group, one coated shell substrate is selected as a test object. The friction coefficient of each group of test objects is measured using a friction coefficient tester: the coating layer of the test object is placed horizontally upward in the friction coefficient tester, and then a 200g weight is placed on the upper surface of the test object, the friction between the test object and the weight is measured, and the friction coefficient of each group of test objects is recorded. (The anti-slip performance is judged by the size of the friction coefficient) The results are shown in Table 2 below.

[0112]

[0113] As shown in Table 2, after being measured by the friction coefficient tester, the friction coefficients of the test objects of Examples 1-3 are all greater than 1.3, while the friction coefficient test results of Comparative Examples 4-5 are significantly less than the test results of Examples 1-3, indicating that the mixed coating of cerium oxide and silicon dioxide can effectively increase the friction coefficient of the surface of the shell substrate, thereby improving the anti-slip performance. Moreover, compared with the single deposition of silicon dioxide coating or cerium oxide coating, the mixed coating of cerium oxide and silicon dioxide is more conducive to increasing the friction coefficient of the surface of the shell substrate, and the cerium oxide and silicon dioxide components synergize with each other, which is more conducive to improving the anti-slip performance.

[0114] Comparative Example 6

[0115] The difference between this comparative example and Example 1 is that in the process of preparing the protective paint for coating the coating layer, the modified mixed nanoparticles in step S4.4 are removed, and the other steps remain unchanged to prepare a laptop computer shell after coating protection, which is recorded as Comparative Example 6.

[0116] Grouping was performed according to each of Examples 1-3 and Comparative Example 6, and 3 laptop computer shells after coating protection were selected from each of Examples 1-3 and Comparative Example 6 as test samples. One test sample was selected from each group as a test object, and the friction coefficient of each group of test objects was measured using a friction coefficient tester: the coating layer of the test object was placed horizontally upward in the friction coefficient tester, and then a 200g weight was placed on the upper surface of the test object to measure the friction between the test object and the weight. The friction coefficient of each group of test objects was recorded. (The anti-slip performance was judged by the size of the friction coefficient)

[0117] The remaining two test samples in each group were tested for wear resistance: first, the contact angle of water on each group of test samples was tested using a contact angle meter, and the average contact angle of each group of test samples before friction was recorded. Subsequently, steel wool was attached to the surface of each group of test samples, and the steel wool was pushed back and forth to rub the surface of each group of test samples. The friction force applied was the same. After 500 back and forth frictions, the contact angle of water on each test sample was tested again using a contact angle meter, and the average contact angle of each group of test samples after friction was recorded. (The wear condition and anti-fouling performance were judged by the change in contact angle before and after friction. Generally, it was greater than 150°, which means it has strong anti-fouling ability) The results are shown in Table 3 below.

[0118]

[0119] As shown in Table 3, after the test objects of Examples 1-3 were measured by the friction coefficient tester, their friction coefficients were all greater than 1.52, while the friction coefficient test result of Comparative Example 6 was 1.41, which was less than the test results of Examples 1-3, indicating that after the coating layer was coated with a protective coating, it could further increase the friction coefficient and improve the surface anti-skid performance of the laptop shell after the coating layer was protected. In addition, the modified mixed nanoparticles in the coating layer coating protective paint played a major anti-skid synergistic role, further improving the anti-skid performance of the laptop shell. Furthermore, from the contact angle results before and after friction, it can be seen that the contact angle of the surface of the laptop shell after the coating layer in Examples 1-3 was greater than 150° and the contact angle before and after friction changed little, with only slight wear and tear, and excellent wear resistance, indicating that the coating layer of the laptop shell after the coating layer protection in Examples 1-3, the coating protective layer attached to the surface of the coating layer can effectively improve the wear resistance and stain resistance of the coating layer, and avoid damage or surface contamination of the coating layer.

[0120] It should be understood that those skilled in the art can make improvements or changes based on the above description, and all such improvements and changes should fall within the scope of protection of the appended claims of the present invention. Parts not described in detail in this specification belong to the prior art known to those skilled in the art.

Claims

1. A non-slip coating process for the surface of a notebook computer housing, characterized in that: The steps include: S1: pretreatment of the shell substrate, ultrasonic cleaning and surface treatment of the shell substrate, so that the surface of the shell substrate is kept clean, and the roughness of the surface of the shell substrate Ra ≤ 0.5 μm; S2: Preparation of AlMnCe alloy target, using high-purity metal Al, Mn, Ce as initial raw materials, after smelting, casting, vacuum degassing, cutting and surface grinding and polishing, AlMnCe alloy target is obtained, wherein the Ce addition amount is 8-12% of the total mass of Al and Mn; S3: Surface vacuum coating processing, after completing the pretreatment of the shell substrate, the shell substrate is placed under vacuum conditions, an inert gas is introduced, and an aluminum target and a titanium target are sputtered onto the surface of the shell substrate to deposit an Al-Ti transition layer. The inert gas is continuously introduced, and an AlMnCe alloy target is sputtered onto the surface of the shell substrate, and an AlMnCe layer is deposited on the Al-Ti transition layer. An inert gas and oxygen are introduced, and a silicon target and a cerium target are sputtered onto the surface of the shell substrate, and a cerium oxide and silicon dioxide mixed coating layer is deposited on the AlMnCe layer. After the coating is completed, only oxygen is introduced, and the shell substrate is heated and heat-insulated to complete the surface vacuum coating processing of the shell substrate, and obtain the shell substrate after the coating processing; S4: preparing a coating layer protective paint and performing a coating layer protective treatment, preparing a coating layer protective paint, and spraying the coating layer protective paint on the surface of the shell substrate after the coating process by electrostatic spraying to form a coating protective layer, thereby obtaining a laptop shell after coating protection; The coating layer is coated with a protective paint prepared by mixing 50 to 70 parts by weight of an organic silicon acrylic resin, 0.5 to 3 parts by weight of an organic silicon defoamer, 0.3 to 2 parts by weight of dimethylsiloxane, 4 to 10 parts by weight of a curing agent, and 2 to 8 parts by weight of modified mixed nanoparticles; The silicone acrylic resin is prepared by stirring and mixing 20 to 30 parts by weight of methyl acrylate, 25 to 40 parts by weight of methyl methacrylate, 20 to 35 parts by weight of styrene, 5 to 12 parts by weight of hydroxyethyl acrylate, 2 to 7 parts by weight of acrylic acid and 0.6 to 3 parts by weight of dibenzoyl peroxide, and then slowly dripping into a mixed solution of ethyl acetate, butyl acetate and polydimethylsiloxane to obtain the organic silicone acrylic resin through a polymerization reaction. The mixed solution of ethyl acetate, butyl acetate and polydimethylsiloxane is prepared by mixing 25 to 35 parts by weight of ethyl acetate, 16 to 40 parts by weight of butyl acetate and 7 to 18 parts by weight of polydimethylsiloxane. The modified hybrid nanoparticles are obtained by mixing nano-silicon dioxide and nano-titanium dioxide and then modifying them with a coupling agent KH-570.

2. The anti-slip coating process for the surface of a notebook computer shell according to claim 1, characterized in that: The shell base material is titanium alloy, aluminum-magnesium alloy or magnesium-aluminum alloy.

3. The anti-skid coating process for the surface of a notebook computer shell according to claim 1, characterized in that: The surface treatment is at least one of a grinding operation, a sandblasting operation or a shot peening operation.

4. The anti-skid coating process for the surface of a notebook computer housing according to claim 1, characterized in that: Step S2: AlMnCe alloy target material preparation, specifically comprising the following steps: S2.1: Using high-purity metals Al, Mn, and Ce as initial raw materials, the mass ratio of Al to Mn is (10-20):(1-5), and the amount of Ce added is 8-12% of the total mass of Al and Mn. In an inert gas atmosphere, Al, Mn, and Ce are melted and mixed into an alloy liquid, and the alloy liquid is poured into a mold for casting to obtain an AlMnCe alloy ingot; S2.2: After vacuum degassing of the AlMnCe alloy ingot, cutting and surface grinding and polishing are performed to obtain the AlMnCe alloy target.

5. The anti-skid coating process for the surface of a notebook computer housing according to claim 4, characterized in that: Step S3: Surface vacuum coating processing, specifically including the following steps: S3.1: After the shell substrate is pretreated, the shell substrate is placed in a vacuum furnace and the vacuum furnace is evacuated to a background vacuum with a vacuum degree of 3 to 6×10 -3 Pa, heat the shell substrate in the vacuum furnace to 70-90°C; S3.2: Load the aluminum target into the sputtering target A, load the titanium target into the sputtering target B, introduce an inert gas into the vacuum furnace, the inert gas flow rate is 200-400 sccm, the gas pressure is controlled at 0.1-1 Pa, and the sputtering power supplies of the sputtering targets A and B are turned on at the same time, the current of the sputtering target A is 25-30A, and the current of the sputtering target B is 20-25A, and the aluminum target and the titanium target are sputtered onto the surface of the shell substrate, so that a layer of Al-Ti transition layer with a thickness of 100-150nm is deposited on the surface of the shell substrate; S3.3: Replace the aluminum target material in the sputtering target A with an AlMnCe alloy target material, continue to introduce an inert gas into the vacuum furnace, the inert gas flow rate is 200-400 sccm, the gas pressure is controlled at 0.1-1 Pa, turn on the sputtering power supply of the sputtering target A, the current of the sputtering target A is 20-30 A, and sputter the AlMnCe alloy target material onto the surface of the shell substrate, and deposit a layer of AlMnCe with a thickness of 150-200 nm on the Al-Ti transition layer; S3.4: Replace the AlMnCe alloy target in sputtering target A with a silicon target, replace the titanium target in sputtering target B with a cerium target, introduce inert gas and oxygen into the vacuum furnace, the inert gas flow rate is 200-400sccm, the oxygen flow rate is 150-300sccm, and the gas pressure is controlled at 0.5-1.5Pa. At the same time, turn on the sputtering power supplies of sputtering target A and sputtering target B, the current of sputtering target A is 25-30A, and the current of sputtering target B is 25-30A. Sputter the silicon target and the cerium target onto the surface of the shell substrate, and deposit a cerium oxide and silicon dioxide mixed coating layer with a thickness of 100-200nm on the AlMnCe layer. The Al-Ti transition layer, the AlMnCe layer, and the cerium oxide and silicon dioxide mixed coating layer together constitute a coating layer from bottom to top; S3.5: After the coating is completed, stop the introduction of inert gas, and only introduce oxygen into the vacuum furnace. The oxygen flow rate is 150-300sccm. The shell substrate is heated at a temperature of 400-600°C and kept warm for 20-30 minutes to complete the surface vacuum coating of the shell substrate and obtain the shell substrate after coating.

6. The anti-skid coating process for the surface of a notebook computer housing according to claim 5, characterized in that: The inert gas is any one of helium, neon, argon, krypton or xenon.

7. The anti-skid coating process for the surface of a notebook computer housing according to claim 5, characterized in that: Step S4 is the preparation of coating protective paint for the coating layer and the coating protective treatment for the coating layer, which specifically includes the following steps: S4.1: 20 to 30 parts by weight of methyl acrylate, 25 to 40 parts by weight of methyl methacrylate, 20 to 35 parts by weight of styrene, 5 to 12 parts by weight of hydroxyethyl acrylate and 2 to 7 parts by weight of acrylic acid are mixed and stirred, and then 0.6 to 3 parts by weight of dibenzoyl peroxide are added, and the mixture is stirred evenly to obtain an acrylic monomer mixture; S4.2: 25-35 parts by weight of ethyl acetate, 16-40 parts by weight of butyl acetate and 7-18 parts by weight of polydimethylsiloxane are sequentially added into a reaction kettle, heated to 72-80° C. under a nitrogen atmosphere, stirred continuously for 20-30 minutes, and then heated to 100-110° C. The acrylic acid monomer mixture obtained in step S4.1 is slowly dripped into the reaction kettle, and polymerized under azeotropic distillation conditions at 100-110° C. for 1-2 hours to obtain a silicone acrylic resin; S4.3: 1 to 5 parts by weight of nano-silicon dioxide and 1 to 5 parts by weight of nano-titanium dioxide are mixed to obtain mixed nano-particles, the mixed nano-particles are dissolved in 20 to 40 parts by weight of N-methylpyrrolidone, and ultrasonically dispersed for 20 to 30 minutes, and then 6 to 30 parts by weight of coupling agent KH-570 are slowly added dropwise under the condition of ultrasonic dispersion, and reacted for 1 to 2 hours under a nitrogen atmosphere. After the reaction is completed, the modified mixed nano-particles are obtained by centrifugal separation, filtration, and washing; S4.4: 50 to 70 parts by weight of silicone acrylic resin, 0.5 to 3 parts by weight of silicone defoamer, and 0.3 to 2 parts by weight of dimethylsiloxane are added to a reactor, and after uniform mixing, 4 to 10 parts by weight of curing agent and 2 to 8 parts by weight of modified mixed nanoparticles are added, and ultrasonic dispersion is performed for 20 to 40 minutes to obtain a coating layer coated with protective paint; S4.5: The coating layer is coated with protective paint by electrostatic spraying on the surface of the shell substrate after coating. Subsequently, the shell substrate after spraying is placed in a drying oven and dried and cured at 50-60°C for 2-5 hours to form a coating protective layer. The coating layer protection treatment is completed to obtain a laptop shell after coating protection.

8. The anti-skid coating process for the surface of a notebook computer housing according to claim 7, characterized in that: The diameter of nano-silicon dioxide is 10 to 80 nm.

9. The anti-skid coating process for the surface of a notebook computer housing according to claim 8, characterized in that: The diameter of nano-titanium dioxide is 10 to 50 nm.

10. The anti-skid coating process for the surface of a notebook computer housing according to claim 9, characterized in that: The curing agent is hexamethylene diisocyanate.